Effect of diets with varying starch content on muscle glycogen concentrations during training and replenishment after highintensity exercise - Mesquita, Vanesa Silva de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Muscle glycogen is an important energy substrate and a potentially limiting factor of performance in horses. Due to the large number of studies using low-starch, high-fat and fiber concentrates for the management of metabolic diseases, the use of such feeds has become widely popular. However, there is scarce evidence of the effectiveness of such feeds on glycogen maintenance and replenishment. To evaluate the effect of three diets varying in starch content on the maintenance of glycogen leveis during a training period and on repletion of glycogen stores after high-intensity exercise, six previously conditioned Thoroughbred horses were used in a 3 x 3 Latin Square design. Horses were fed (at 1 kg/100kg BW/day) either a high-starch (HS), a moderately starch-rich, high-fat concentrate (MS) or a low-starch, high-fat and fiber concentrate (LS). Forage was fed at 1.25 kg/100 kg BW/day in ali treatments. Horses were trained for three weeks and then underwent three days of strenuous exercise designed to substantially deplete glycogen reserves, and were subsequently observed over four days of recovery. Muscle biopsies were obtained before depletion and at 0, 24, 48 and 72 hours post-depletion. Day one of depletion was an incremental exercise test (IET) and blood was sampled at each speed step for plasma glucose and lactate. During the IET horses wore a loose-fit mask for assessment of Oxygen consumption (V02), Carbon Dioxyde production (VCO2) and Respiratory Exchange Ratio (RER). A submaximal exercise test was performed both before and after depletion of glycogen reserves to verify alterations in energy substrate utilization due to depletion. Plasma glucose, lactate and RER during the IET were not different among treatments. RER during the submaximal exercise test were lower for the LS treatment (P<0.05). Post-depletion RER for HS and MS were different from pre-depletion RER in the submaximal test ...

O glicogênio muscular é uma importante fonte de energia e uma fator potencialmente limitante do desempenho equino. Devido ao grande número de estudos usando concentrados de baixo amido e alta fibra e gordura para o manejo de distúrbios metabólicos, o uso de tais concentrados se tornou prática popular. Entretanto, há pouca evidência sobre a eficiência de tais concentrados sobre a manutenção e a reposição das concentrações de glicogênio muscular. Para avaliar o efeito de três dietas com conteúdo diferente de amido sobre a manutenção do glicogênio muscular durante um período de treinamento e sobre a repleção das reservas de glicogênio após exercício de alta intensidade, seis cavalos Puro-Sangue Inglês previamente condicionados fisicamente foram usados em um delineamento Quadrado Latino 3x 3. Os cavalos receberam 1 kg/100 kg de PV/dia de um concentrado com conteúdo de amido alto (HS), moderado (MS) ou baixo (LS). A forragem foi fornecida a uma taxa de 1.25 kg/100 kg PV/dia em todos os tratamentos. Os cavalos foram treinados por 3 semanas e então foram submetidos a três dias de exercício intenso programado para depletar substancialmente as reservas de glicogênio, e foram subsequentemente observados durante 4 dias de recuperação. Biópsias musculares foram obtidas antes da depleção e O, 24, 48 e 72 horas após a depleção. O primeiro dia de depleção consistiu em um teste incremental (IET) e sangue foi amostrado a cada etapa de velocidade para análise de glicose e lactato. Durante o IET os cavalos usaram uma máscara para verificação do consumo de Oxigênio (V02), da produção de Dióxido de Carbono (VCO2) e do coeficiente respiratório (RER). Um teste submáximo de esforço foi realizado antes e depois da depleção das reservas de glicogênio para investigar alterações na utilização dos substratos energéticos em função da depleção. A glicose plasmática e o RER ...
Keywords: Equino; Cavalo; Cavalo - Nutrição; Amido; Glicogenio; Starch